The influence of anaemia on the results of chemoradiotherapy in cervical cancer patients - Jakubowicz, Jerzy; Reinfuss, Marian; Blecharz, Paweł; Skotnicki, Piotr; Szatkowski, Wiktor; Krzystek-Małecka, Halina (Contemporary Oncology/Współczesna Onkologia, 2008)
The paper presents the problem of anaemia in patients with carcinoma of the cervix, with special consideration to patients receiving chemoradiotherapy. Based on data obtained from the literature, the authors determined the frequency of anaemia occurrence (haemoglobin concentration below 12g/dl) in this group of patients, its association with the primary tumour oxygenation status and its prognostic significance. The paper also contains an assessment of anaemia compensation methods (transfusions, administration of erythropoietin) and the possible effect of such compensation on survival.